Od kronologije prema teorijskim konceptima - iseljenička problematika u hrvatskoj historiografiji na uzorku radova objavljenih u Časopisu za suvremenu povijest - Hrstić, Ivan; Marinović Golubić, Marica (2019)
U članku se na temelju 39 radova posvećenih iseljeničkoj tematici, objavljenih u Časopisu za suvremenu povijest od 1969. do 2018., analizira istraženost povijesti hrvatskoga iseljeništva unutar hrvatske historiografije. Analiza je provedena na dvije razine. S jedne strane problematizirana je opća (pod)zastupljenost navedene tematike u kontekstu cjelokupne hrvatske historiografije, a potom je postavljeno pitanje utjecaja dominantnoga narativa na istraživanje kroz tri ključne domene: izbor tema, upotreba karakteristične metodologije te sama interpretacija. Pritom su odvojeno promatrana dva razdoblja, za vrijeme Socijalističke Federativne Republike Jugoslavije te po ostvarenju samostalnosti Republike Hrvatske. Usporedno s tim dijelom analize osnovne karakteristike radova na temu hrvatskoga iseljeništva kontekstualizirane su s dosezima stranih historiografija te srodnih znanstvenih disciplina s aspekta primjene teorijskih i metodoloških okvira istraživanja.
This article encompasses an analysis of research on the process of the formation and development of Croatian émigré communities in Croatian historiography based on 39 papers devoted to this topic, published from 1969 to 2018. The analysis was conducted on two levels. The general (under)representation of the topic in the context of Croatian historiography as a whole is examined first, followed by the issue of the influence of the dominant narrative on research through three key domains: the selection of topics, the use of characteristic methodology, and the interpretation itself. In this context, two periods have been examined separately – during the Socialist Federal Republic of Yugoslavia and after the Republic of Croatia achieved independence. Parallel with this part of the analysis, the basic characteristics of papers on the topic of Croatian émigrés have been contextualised in regard to the achievements of foreign historiography and related scientific disciplines from the aspect of applying theoretical and methodological research frameworks. The reasons for the poor representation of this topic include high politicisation in regard to the critical stance of a large part of the émigré population towards the political system in Yugoslavia till 1991 and the difficult accessibility of archival material and relevant literature on immigrant associations. The analysis did not find any direct influence of politics, i.e. ideology, on the researchers, but there was a shift in the focus of research in line with changes in the social context, from the (pro-)Yugoslav émigré communities towards the predominantly anti-Yugoslav ones in works published after 1991. The predominant characteristic of the analysed works in both periods is the lack of an interpretation of the activities of examined individuals, events, and processes in a broader theoretical framework.
Bibliografske bilješke uz tekst ; bibliografija: str. 379-383.
Sažetak ; Summary.
Keywords: Časopis za suvremenu povijest; Hrvatsko iseljeništvo -- Historiografija -- Društvena povijest -- Interdisciplinarnost